A Cationic Porphyrin, ZnPor, Disassembles Pseudomonas aeruginosa Biofilm Matrix, Kills Cells Directly, and Enhances Antibiotic Activity of Tobramycin - Neha Patel; Shawn Swavey; Jayne Robinson (MDPI AG, 2020)
One of the greatest threats to human health is the rise in antibiotic-resistant bacterial infections. Pseudomonas aeruginosa (PsA) is an "opportunistic" pathogen known to cause life-threatening infections in immunocompromised individuals and is the most common pathogen in adults with cystic fibrosis (CF). We report here a cationic zinc (II) porphyrin, ZnPor, that effectively kills planktonic and biofilm-associated cells of PsA. In standard tests against 16-18 h-old biofilms, concentrations as low as 16 µg/mL resulted in the extensive disruption and detachment of the matrix. The pre-treatment of biofilms for 30 min with ZnPor at minimum inhibitory concentration (MIC) levels (4 µg/mL) substantially enhanced the ability of tobramycin (Tobra) to kill biofilm-associated cells. We demonstrate the rapid uptake and accumulation of ZnPor in planktonic cells even in dedicated heme-uptake system mutants (ΔPhu, ΔHas, and the double mutant). Furthermore, uptake was unaffected by the ionophore carbonyl cyanide m-chlorophenyl hydrazine (CCCP). Cells pre-exposed to ZnPor took up the cell-impermeant dye SYTOXTM Green in a concentration-dependent manner. The accumulation of ZnPor did not result in cell lysis, nor did the cells develop resistance. Taken together, these properties make ZnPor a promising candidate for treating multi-drug-resistant infections, including persistent, antibiotic-resistant biofilms.